Evaluating student evaluations: evidence of gender bias against women in higher education based on perceived learning and instructor personality - Khokhlova, Olga; Lamba, Nishtha; Kishore, Sameer (Frontiers in Education, 2023)
Given student evaluations are an integral part of academic employment and progression in higher education, it is crucial to explore various biases amongst students that may influence their ratings. Several studies report a clear gender bias in student evaluation where male instructors receive significantly higher ratings as compared to female instructors. However, there is very limited research about gender biases in underrepresented samples such as South Asia and the Middle East.We examined whether perception of male and female instructors differed in terms of how they facilitate learning and level of engagement, using an experimental design. 671 university students were asked to watch a video of an online lecture on psychology, delivered by either a male or female lecturer, after which they were asked to evaluate their experience and instructor personality characteristics. To ensure consistency across content, tone, delivery, environment, and overall appearance, photorealistic 3D avatars were used to deliver the lectures. Only gender as a factor was manipulated. Given the racial representation in the region, a total of four videos were developed representing males (n = 317) and females (n = 354) of White and South Asian race.Overall, male instructors scored significantly higher in variables representing personality characteristics such as enthusiasm and expressiveness compared to female instructors.Participants did not however view male and female instructors to be different in terms of presentation and subject knowledge. Findings related to facilitating learning suggest that male instructors were perceived to have made instructions more interesting, kept participants' attention for longer, and were more interesting compared to female instructors. In terms of engagement, male instructors were perceived to be more expressive, enthusiastic, and entertaining, compared to female instructors.Given the experimental design, these findings can clearly be attributed to gender bias, which is also in line with previous research. With an underrepresented sample, an online platform delivery, 1 Khokhlova et al.and inclusion of multiple races, these findings significantly add value to the current literature regarding gender stereotypes in higher education. The results are even more concerning as they provide evidence of gender bias which may contribute to subconscious discrimination against women academics in the region.